Evolutionary algorithms for global optimization and dynamic system diagnosis - Obuchowicz, Andrzej (Zielona Góra: Lubusky Scientific Society)
The aim of this monograph is to present selected basic properties of evolutionary algorithms in the global optimization and chosen applications in the neutral networks design problem and the fault diagnosis of industrial processes.
Keywords: algorytmy genetyczne; programowanie dynamiczne